Synthesis characterization and antibacterial activity of Cr (III), Co (III), Fe (II), Cu (II), Ni (III) complexes of 4-(2-(((2-hydroxy-5-nitrophenyl) diazenyl) (phenyl) methylene) hydrazinyl) benzene sulfonic acid based formazan dyes and their applications on leather. (January 2018) - Khan, Shakeel Ahmad; Shahid, Sammia; Kanwal, Sadia; Hussain, Ghulam
Abstract: A novel series of un-metallized and metal complexes formazan dye (12–17 ) have been synthesized in an aqueous system, without using Buffers, with cost-effectiveness and improved fastness properties. The synthetic methodology involved the synthesis of 4-(2-(((2-hydroxy-5-nitrophenyl) diazenyl) (phenyl) methylene) hydrazinyl) benzene sulfonic acid followed by diazotization of 4-nitroamisnophenol which further coupled with coupler reagent i.e. 4-[(2Z)-2-benzylidenehydrazinyl] benzene sulfonic acid. Multichromic metal complexes of 4-(2-(((2-hydroxy-5-nitrophenyl) diazenyl) (phenyl) methylene) hydrazinyl) benzene sulfonic acid (1:1 and 2:1) were synthesized with the salts of Chromium, Iron, Cobalt, Copper and Nickel. Newly synthesized metal complexes were characterized by Ultraviolet–visible (UV–Vis), Fourier transforms infrared (FT-IR), Proton nuclear magnetic resonance ( 1 H NMR), C 13 -nuclear magnetic resonance ( 13 C NMR), powder X-ray crystallography (XRD) and elemental analysis. Their performance as colorant material for different fastness properties like light fastness, wash fastness, perspiration fastness were evaluated on leather fabric and were shown to possess good fastness properties 3–5, 4–5, 3–5, and 4–5 respectively. The synthesized formazan dyes were also demonstrated the high percentage value of exhaustion and fixation on leather ranging from 91–97% and 90–98% respectively. The synthesized un-metallized and metal complex formazan dyes were ranged in color from Blue, violet, Green, Brown to Red. Antibacterial activity of synthesized formazan dyes was determined in solution by agar well diffusion method and on leather using the dyed leather fabric with synthesized dyes as model system. Maximum antibacterial activity in solution with ZOIs (19 ± 0.05 mm, 25 ± 0.07 mm, 23 ± 0.09 mm, 27 ± 0.03 mm) and significant % reduction in bacterial growth on leather (56 ± 0.03%, 65 ± 0.07%, 70 ± 0.05%, and 72 ± 0.08%) was demonstrated by chromium complex (15 ) against E. coli, S. aureus, Klebsiella and B. subtilis respectively. Graphical abstract: Highlights: Metal Complexes of novel formazan dyes were synthesized with Cr (III), Co (III), Fe (II), Cu (II) and Ni (III). Synthesized formazan dyes produced different coloration on leather from Blue, Violet, Green, Brown to Red. Excellent fastness, fixation and exhaustion properties were observed by the synthesized formazan dyes. Antibacterial activity of novel formazan dyes determined in solution and on leather by agar diffusion method.